COMPARISON THE REAL COST WITH INA-CBG’S PACKAGE TARIFF AND ANALYSIS ON THE FACTORS INFLUENCING THE REAL COST FOR DIEBETES MELLITUS INPATIENTS USING JAMKESMAS IN RSUP Dr. SARDJITO YOGYAKARTA - Ratih Pratiwi Sari; Fita Rahmawati; I Dewa Putu Pramantara (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
The problem usually found in the Jamkesmas (Society Health Insurance) realization is the difference between the real cost and INA-CBGs package tariff for patients using Jamkesmas, especially in inpatient department. This study was to find out how much the margin between the real cost and the INA-CBG’s package tariff and the factors influence the real cost, and to know the suitability of drug indications in diabetes mellitus inpatients using Jamkesmas in RSUP Dr. Sardjito Yogyakarta. This study was analytical observation. The data were taken retrospectively from the Jamkesmas claim files and patients’ medical record. Subjects were patients with diabetes mellitus type 2.The research object included the claim files and the medical record of the diabetes mellitus patients using Jamkesmas in RSUP Dr. Sardjito Yogyakarta during period of July 2010 – May 2012 with the diagnosis code INA-CBGs E-4-10-I, E-4-10-II, and E-4-10-III. The data were analyzed descriptively. Moreover, One sample test statistical analysis was conducted to find the difference between the real cost and INA-CBGs tariff and the ifference between hospital LOS and INA-CBGs package LOS. In addition,bivariate correlation test and regression linier test were used to study the relation among the factors that affect the real cost. The result of the study showed that the difference between the real costand INA-CBGs package tariff of the diabetes mellitus Jamkesmas patients with the severity level I was Rp 5,325,126 in 2 episodes of cares; severity level II was Rp -22,411 in 10 episodes of care, and severity level III was Rp -3,038,240 in 12 episodes of care. The factors that affect the real cost of treatment of patients with the severity level II were cost of clinical pathology examination, blood, and drug/medical cost, while in patient with severity level III werethe cost of visite, service in dialysis department, clinical pathology examination and drug/medical cost. From the analysis between the used drug and indication, it was found that 22 episodes of care was appropriate with the diagnosis and 2 episodes of care was not fit with the diagnosis.Keywords: Jamkesmas, INA-CBG’s, diabetes mellitus, cost components, indication of suitability